OT BALIĞI'NDA TAM KONTROLLÜ DÖL ALIMI - AKKAYA, AYŞE GÜL ERDEM (Fırat Üniveristesi, 2006)
Bu çalışma ile ot balığından tam kontrollü yöntemle alınan yumurtalarda gerçek sayımmetodu kullanılarak 1kg yumurta ağırlığına düşen yumurta sayısı ortalama 844.000 adet olarakbelirlendi. Döllenme işlemini takiben, her biri 7L kapasitedeki 12 zuger şişesine 20'şer gramyumurta yerleştirildi. Kuluçkalamaya başladıktan 2.5 saat, sonra gerçek sayım yöntemiyle döllenenortalama yumurta oranı sırası ile %80.4, %80.6, %80.2, kontrol grubunda %80.4; döllenmeyenyumurta oranı sırası ile %19.6, %19.4, %19.8, kontrol grubunda %19.6; döllenen yumurtalarüzerine kuluçkalanma esnasında üç farklı (2ml/L, 3ml/L, 4ml/L) konsantrasyonda hazırlanmışalkali proteaz (Alcalase-Bacillus licheniformis) enzimi uygulandı. Enzim uygulanan gruplardakikuluçkalanma süresi 18 saat, kontrol grubunda 24 saat; enzim uygulanan gruplardaki açılanortalama yumurta oranı sırası ile %94.2, %95.3, %95.4, kontrol grubunda %94; açılmayan ortalamayumurta oranı sırası ile %5.8, %4.7, %4.6, kontrol grubunda %6; enzim uygulanan gruplardalarvaların ortalama yaşama oranı sırası ile %80.8, %80.8, %79.2, kontrol grubunda %78.8;larvaların ölüm oranı sırası ile %19.2, %19.2, %20.8, kontrol grubunda %21.2; larvaların yumurta(besin) keselerini absorbe etme süreleri 4 gün olarak belirlenmiştir.Sonuç olarak kullanılan 16880 adet yumurta sayısı dikkate alındığında döllenen yumurtasayısı, açılan yumurta sayısı ve canlı larva sayısı bakımından uygun olabileceği kanaatinevarılmıştır.Anahtar Kelime: Ot balığı, Ctenopharyngodon idella, üretim, döllenme, döl alımı, alkaliproteaz.

In this study, it was aimed to determine the eggs number, rates of fertilized and infertilized eggsand the effects of three different concentrations (2, 3 and 4 ml/L) of alkali protease (Alcalase-Bacilluslicheniformis) on incubation duration, hatched eggs rate, living larvae rate and the duration of egg sacabsorption of larvae on eggs obtained entirely controlled method from grass carp. For this purpose, carppitiutary was injected to both male and female and their sperm and eggs were obtained. Total 12 zuggerjars with 7 liter capacity each were used for incubation of fertilized eggs. Incubation water hadtemperature 23ºC, pH 7.8 and dissolved oxygen 8 mg/L.Absolute egg numbers were determined as 844 for 1 kg fish weight. Fertilization rate was foundaverage 80.4%. Hatching rates in the eggs kept in 2, 3 and 4 ml/L alkali protease during incubation were94.2%, 95.3% and 95.4% respectively. It was 94% for control group. In addition, living rates were 80.8%,80.8% and 79.2% respectively. It was 78.8% for control group.There was not statistically significant differences among fertilization rates (p>0.05). But, thedifferences among hatching rates and among living larvae rates were statistically found significant(p<0.05) as a result of treatment with different alkali protease concentrations of eggs during incubationperiod.In conclusion, in terms of fertilized, eggs hatched eggs and a live larvae number of 16880 eggsused, 3ml/L concentration of alkali protease has better effect on grass carp eggs compared with otherconcentrations.Key Words: Grass carp, Ctenopharyngodon idella, reproduction, fertilization, spawning, alkaliprotease.I
Entirely controlled reproduction of grass carp
Keywords: Su Ürünleri